Comparative Study of Anthropometric Measurements between Rural and Urban Girls of Madhya Pradesh: Anthropometric Differences Between Rural and Urban Girls in Madhya Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Background Health is men's greatest wealth, he who has health must cherish it with care, least he should lost it. To this end he must have adequate knowledge of how to live health. Objectives of the study 1) To characterize the anthropometric measurements of rural and urban girls of Madhya Pradesh .2) the second objective of the study was to compare anthropometric measurements of rural and urban girls of Madhya Pradesh. Materials and Methods Randomly selected 500 rural and 500 urban girls of Madhya Pradesh and Age group of the subject 13 to 18 years. Conclusions Significant difference was found between Urban and Rural Girls of Madhya Pradesh in relation to Triceps Skin Fold Width. Insignificant difference was found between Urban and Rural Girls of Madhya Pradesh in relation to Body Weight, Stature Height, Elbow Width (Diameter), Knee Width,(Diameter), Upper - Arm Circumference, Fore - Arm Circumference, Thigh Circumference, Calf Circumference, Biceps Skin fold Width, Thigh Skin fold width, Calf Skin fold width.